2016
DOI: 10.1158/0008-5472.can-15-2468
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma Cells Block PEDF Production in Fibroblasts to Induce the Tumor-Promoting Phenotype of Cancer-Associated Fibroblasts

Abstract: Summary Loss of pigment epithelium-derived factor (PEDF, SERPINF1) in cancer cells is associated with poor prognosis and metastasis, but the contribution of stromal PEDF to cancer evolution is poorly understood. Therefore, we investigated the role of fibroblast-derived PEDF in melanoma progression. We demonstrate that normal dermal fibroblasts expressing high PEDF levels attenuated melanoma growth and angiogenesis in vivo, whereas PEDF-depleted fibroblasts exerted tumor-promoting effects. Accordingly, mice wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 50 publications
0
24
1
Order By: Relevance
“…Hematoxylin and eosin (H&E) staining analyses showed that cRGD‐PS‐DM1 nano‐prodrug did not induce obvious damage to the major organs of treated mice (Figure S4, Supporting Information), corroborating that this nano‐prodrug formulation has a low systemic toxicity. B16F10 melanoma is known as a highly aggressive malignancy . The high treatment efficacy and low side effects of cRGD‐PS‐DM1 nano‐prodrug in B16F10 tumor‐bearing mice suggests that this nanodrug platform has a great potential for cancer chemotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…Hematoxylin and eosin (H&E) staining analyses showed that cRGD‐PS‐DM1 nano‐prodrug did not induce obvious damage to the major organs of treated mice (Figure S4, Supporting Information), corroborating that this nano‐prodrug formulation has a low systemic toxicity. B16F10 melanoma is known as a highly aggressive malignancy . The high treatment efficacy and low side effects of cRGD‐PS‐DM1 nano‐prodrug in B16F10 tumor‐bearing mice suggests that this nanodrug platform has a great potential for cancer chemotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work established interactions between melanoma cells and the tumor microenvironment via secreted factors in mice (Nwani et al., ). Furthermore, proteome analyses of exosomes released by melanoma cell lines revealed their impact on melanoma invasiveness through interactions between malignant cells and the tumor microenvironment (Lazar et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…This data suggests that the CAF may produce soluble factors in the medium to promote NSCLC cell survival under stress of chemotherapy drugs. To further determine the key factors in the CAF‐secreted cytokines involved in NSCLC drug resistance, we screened the expression of IGF2 , SDF‐1 , HGF , VEGF α, FGF , EGF , PDGF , CTGF , Tenascin , TSP‐1 and Fibronectin in the CAF pre‐co‐cultured with or without LCP1 cells and found that IGF2 , VEGFa and EGF were significantly upregulated, especially the IGF2 (Figure C). Moreover, we used the recombinant IGF2 to pre‐treat LCP1 and A549 cells, followed by cisplatin, etoposide and vinorelbine diatrate treatment.…”
Section: Resultsmentioning
confidence: 99%